Ideology in the Middle Ages - Sabate, Flocel (CARMEN monographs and studies., 2019)
This highly interdisciplinary volume, with a focus on southern European case studies, sets out to illuminate medieval thought, and to consider how the underlying values of the Middle Ages exerted significant influence in medieval society in the West.